2021
DOI: 10.1155/2021/5514073
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Urinary Phthalate Metabolites with Cardiometabolic Risk Factors and Oxidative Stress Markers in Children and Adolescents

Abstract: Introduction. Studies have proved that exposure of adults to phthalates might be related to cardiometabolic risk factors and changes in markers of oxidative stress. Such studies conducted on school-age children and adolescents are limited and fail to assess the simultaneous effect of phthalates on these risk factors and oxidative stress markers. Therefore, it was attempted to identify the relationship of urinary phthalate metabolites with cardiometabolic risk factors and oxidative stress markers in children an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…This suggests that different effects can be seen at different doses rather than a linear dose-response relationship. A negative association between insulin resistance and MMP in children was reported by Hashemi et al [ 61 ]. It has been reported that insulin resistance and compensatory hyperinsulinemia may lead to increased blood pressure by causing sympathetic system activation, vascular changes, insufficient vascular dilatation and changes in membrane ion exchange [ 72 74 ].…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…This suggests that different effects can be seen at different doses rather than a linear dose-response relationship. A negative association between insulin resistance and MMP in children was reported by Hashemi et al [ 61 ]. It has been reported that insulin resistance and compensatory hyperinsulinemia may lead to increased blood pressure by causing sympathetic system activation, vascular changes, insufficient vascular dilatation and changes in membrane ion exchange [ 72 74 ].…”
Section: Discussionmentioning
confidence: 77%
“…Studies evaluating the relationship between urinary phthalates and blood pressure in children and adolescents are limited and reported controversial results. While an increased risk for blood pressure was found in some studies with urinary MBzP levels in children [ 61 ] and adults [ 62 ], no correlation was observed in others [ 63 , 64 ]. In a cross-sectional study of 108 children aged 6–18 years, a positive correlation was reported between urinary MBzP level and systolic blood pressure [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Urine samples were also taken from the subjects for the creatinine test performed by the Hitachi 704 automatic analyzer [ 6 , 19 ]. A total of 6 ml of urine sample was kept in glass containers at −20°C until the day of the experiment to measure the TCC and 2,4-DCP concentration [ 44 , 51 53 ].…”
Section: Methodsmentioning
confidence: 99%
“…Exposure to phthalate seems to increase oxidative stress levels, which is recognized to contribute to male and female infertility. Phthalates are substances that exhibit endocrine disrupting properties and can induce problems related to infertility, disorders of the metabolic, immune, and thyroid systems [1]. They are a family of esters of phthalic acid, widely used in industry as plasticizing agents, added to improve the flexibility and moldability of plastics and widely used in children's toys, medical devices, cosmetics, hygiene products, clothing such as footwear and raincoats, food packaging, and also construction material [2].…”
Section: Introductionmentioning
confidence: 99%